The Effectiveness of Ponseti Technique in the Management of Club Foot at Two Months - IRAM CHAUDHRY MUHAMMAD KAMRAN SHAFI AD, MOHAMMAD RAFIQ SABIR (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Clubfoot deformity in children is difficult to treat because of complex pathological anatomy of the growing foot. In early weeks of life the treatment of choice is always conservative. Thus, the manipulation and casting techniques of KITE and PONSETI are commonly use with good outcome. We have compared only the short-term results of these two methods by conducting a randomized control trial. Objective: Comparison of KITE with PONSETI method for the treatment of clubfoot in means of passive range of dorsiflexion of ankle joint after treatment at two months. Material and Methods: Randomized controlled trial conducted for eight months at Department of Orthopaedics Bahawal Victoria Hospital Bahawalpur. Results: A total of 100 patients with grade-II clubfoot deformity were recruited and divided into two groups for comparison of both techniques. The data was collected and than analyzed. The mean age in-group A was 26.02 weeks and in-group B was 26.05. In-group A 66.67% were male and 33.33% were female while in-group B 75% male and 25% were female. In-group A 75% of the patient had > 250 passive range of dorsiflexion and in group B 89.58% had the same range of motion. In group A 25% and in group B 10.42% could not meet this criteria. Conclusion: Conservative treatment with PONSETI technique is the best treatment option for clubfoot at an early age.